(untitled) (Research, Society and Development, 2022)
The purpose of this study was to evaluate the occurrence of excess body fat and its associated factors in freshman from a public university in the Northeast of Brazil. This is a cross-sectional analytical study involving 231 freshman with body fat percentage evaluated by electrical bioimpedance, being defined as excess values above 15% for men and 23% for women. The conceptual model considered sociodemographic, anthropometric, dietary and lifestyle variables. The results showed a predominantly female sample (71,4%), mean age of 20.0 ± 4.2 years and 53,7% belonging to the middle class. It was evidenced a high prevalence of excess body fat (48,0%) and after adjustment for Poisson Regression, were independently associated with excess body fat: overweight, abdominal obesity, body perception of being above weight and the use of food in stress situations. The high prevalence of excess body fat is a warning given the youth of the population evaluated and shows the need to insist on primary and secondary prevention measures.